Level of Sensory Integration Problems among People with Autism Spectrum Disorder from the Viewpoint of Their Teachers in Jeddah - Mustafa Houran Al-Qusayreen, Alham (International Journal of Psychosocial Rehabilitation, 2020)
The study aimed to show the level of sensory integration problems among people with autism spectrum disorder from the viewpoint of their teachers in Jeddah (Saudi Arabia). The study sample consisted of 63 male and female teachers working in special education centers and societies that deal with people with autism spectrum disorder. The researcher used the descriptive approach and a questionnaire of 45 items and five dimensions, including audio dimension, visual dimension, taste dimension, smell dimension, and kinesthetic dimension. The validity and reliability of the instrument were verified. The results showed that there were no differences in determining the level of sensory integration problems for people with autism spectrum disorder from the viewpoint of their teachers in Jeddah, according to the gender variable and the educational qualification and experience.